Planning and Development Strategy of Pancer Door Beach Tourism Area in Pacitan City - Irfan Maulana Ashgaf; Lisa Dwi Wulandari (Jurnal Mahasiswa Jurusan Arsitektur, 2022)
Pacitan is a city nicknamed as